Bee foraging preferences, microbiota and pathogens revealed by direct shotgun metagenomics of honey. (20th May 2022) - Galanis, Anastasios; Vardakas, Philippos; Reczko, Martin; Harokopos, Vaggelis; Hatzis, Pantelis; Skoulakis, Efthimios M. C.; Pavlopoulos, Georgios A.; Patalano, Solenn
Abstract: Honeybees ( Apis mellifera ) continue to succumb to human and environmental pressures despite their crucial role in providing essential ecosystem services. Owing to their foraging and honey production activities, honeybees form complex relationships with species across all domains, such as plants, viruses, bacteria and other hive pests, making honey a valuable biomonitoring tool for assessing their ecological niche. Thus, the application of honey shotgun metagenomics (SM) has paved the way for a detailed description of the species honeybees interact with. Nevertheless, SM bioinformatics tools and DNA extraction methods rely on resources not necessarily optimized for honey. In this study, we compared five widely used taxonomic classifiers using simulated species communities commonly found in honey. We found that Kraken 2 with a threshold of 0.5 performs best in assessing species distribution. We also optimized a simple NaOH‐based honey DNA extraction methodology (Direct‐SM), which profiled species seasonal variability similarly to an established column‐based DNA extraction approach (SM). Both approaches produce results consistent with melissopalinology analysis describing the botanical landscape surrounding the apiary. Interestingly, we detected a strong stability of the bacteria constituting the core and noncore gut microbiome across seasons, pointing to the potential utility of honey for noninvasive assessment of bee microbiota. Finally, the Direct‐SM approach to detect Varroa correlates well with the biomonitoring of mite infestation observed in hives. These observations suggest that Direct‐SM methodology has the potential to comprehensively describe honeybee ecological niches and can be tested as a building block for large‐scale studies to assess bee health in the field.